2023
DOI: 10.1002/ps.7814
|View full text |Cite
|
Sign up to set email alerts
|

Spraying performance of umbrella wind‐field‐type atomization and its application to parameter optimization

Shaobo Li,
Jianping Li,
Ruirui Zhang
et al.

Abstract: BackgroundHere we designed an umbrella wind‐field‐type anti‐drift spraying device to improve droplet deposit in the fruit tree canopy, reduce spray drift between fruit tree rows, and avoid uneven droplet deposit in the canopy.ResultsWe use Computational Fluid Dynamics combined with wind field test to optimize the parameters of the anti‐drift spray device, and the results show that airflow velocity at the outlet of the device after optimization is 24.5 m/s, which is 48% higher than that before optimization (16.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In order to control droplet drift, anti-drift components are usually fitted to the sprayer. [21][22][23] The most common use of anti-drift devices is to add a shield to the sprayer. 24 It has been shown that shields provide better protection against droplet drift.…”
Section: Introductionmentioning
confidence: 99%
“…In order to control droplet drift, anti-drift components are usually fitted to the sprayer. [21][22][23] The most common use of anti-drift devices is to add a shield to the sprayer. 24 It has been shown that shields provide better protection against droplet drift.…”
Section: Introductionmentioning
confidence: 99%